Children, youth and participatory arts for peacebuilding : lessons from Kyrgyzstan, Rwanda, Indonesia and Nepal - Breed, Ananda; Marambio, Helena-Ulrike; Pells, Kirrily; Timalsina, Rajib (Abingdon, Oxon : Routledge, 2024)
"This book demonstrates how participatory arts-based approaches can help children and youth contribute to peacebuilding within post-conflict contexts and to their communities. Cultural forms of storytelling through visual arts, drama, music, and dance can help to enhance post-conflict community wellbeing, social cohesion, and conflict prevention. However, in the planning and implementation of these arts-based projects, children and youth are often marginalised in decision making processes. Drawing on cases from Kyrgyzstan, Rwanda, Indonesia and Nepal, this book demonstrates the benefits of participatory action research with children and youth to inform education curricula and policies for sustaining peace. Showing how artforms can be adapted to meet the needs of children and youth, the book emphasises the need to scale-up arts-based peacebuilding initiatives and leverage for greater policy enactment from the bottom-up. It is also an excellent example of South-South learning, advocating for a local approach to engage with arts-based methodologies and peacebuilding. This book will be of interest to researchers across the applied arts, sociology, anthropology, political science, peacebuilding, and international development. Practitioners and policy makers would also benefit from the book's recommendations for the implementation of successful arts-based research projects and interventions"--
Contesting constructions of childhood and youth in policy and practice for peacebuilding / Ashley Cunningham, Solinda Morgillo and Kirrily Pells -- Cultural arts and participatory peacebuilding for inclusion and social justice in Nepal / Bishnu Khatri and Rajib Timalsina -- Youth section / Eric Ngabonziza, Juhi Adhikari, Leonard Nyiringabo, Laura H.V. Wright and Laura Lee.
Keywords: Arts and children; Arts and youth; Peace-building.; SOCIAL SCIENCE / Third World Development